1989
DOI: 10.1002/ana.410250312
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a new tissue plasminogen activator analogue, Fb‐Fb‐CF, on cerebral reperfusion in a rabbit embolic stroke model

Abstract: Early fibrinolytic therapy with full molecular tissue plasminogen activator (t-PA) has been observed to be both angiographically and clinically effective when employed in animal stroke models. Preliminary clinical trials with t-PA are in progress. It is possible to refine t-PA by developing fragments or analogues of the drug. Using recombinant DNA technology in the Escherichia coli system, a t-PA analogue consisting of the catalytic fragment of t-PA and a dimer of the B fragment of staphylococcal protein A (Fb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Del Zoppo et al, 30 working with baboons, found no increased liability to intracerebral hemorrhage in treated animals over controls when t-PA treatment was given after 3 hours of MCA occlusion followed by 30 minutes of reperfusion. On the other hand, Lyden et al 8 found intracerebral hemorrhages in rabbits receiving 3-5 mg/kg t-PA over 30 minutes, whether this was commenced at 10 minutes, 8 hours, or 24 hours after embolization, while Phillips et al 14 saw hemorrhagic transformation of strokes in rabbits receiving a bolus of 0.8 mg/kg t-PA analogue either 15 or 90 minutes after embolization. These findings leave it uncertain to what extent the total dose of t-PA, its speed of administration, and the length of subsequent survival contribute to the finding of hemorrhagic change within the infarct of animals treated with thrombolytic agents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Del Zoppo et al, 30 working with baboons, found no increased liability to intracerebral hemorrhage in treated animals over controls when t-PA treatment was given after 3 hours of MCA occlusion followed by 30 minutes of reperfusion. On the other hand, Lyden et al 8 found intracerebral hemorrhages in rabbits receiving 3-5 mg/kg t-PA over 30 minutes, whether this was commenced at 10 minutes, 8 hours, or 24 hours after embolization, while Phillips et al 14 saw hemorrhagic transformation of strokes in rabbits receiving a bolus of 0.8 mg/kg t-PA analogue either 15 or 90 minutes after embolization. These findings leave it uncertain to what extent the total dose of t-PA, its speed of administration, and the length of subsequent survival contribute to the finding of hemorrhagic change within the infarct of animals treated with thrombolytic agents.…”
Section: Discussionmentioning
confidence: 99%
“…14 However, streptokinase proved ineffective in causing clot lysis in the cerebral arteries of a rabbit model, whether given immediately 11 or 3 hours 15 after embolization. Moreover, the use of either streptokinase 16 or urokinase 17 ' 18 in the treatment of acute cerebral infarction in humans was sometimes followed by the development of hematomas intracranially or elsewhere, as well as being without demonstrable therapeutic benefit.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Just before the onset of treatment, angiography was performed a third time to document persistent arterial occlusion. Angiography was performed again 30 minutes after treatment was finished and repeated four more times at by guest on May 11, 2018 http://stroke.ahajournals.org/ 4 This analogue consists of the catalytic fragment of the t-PA molecule, including amino acid 262 from the amino terminal of the molecule to the carboxyl terminal, and fragment B of staphylococcal protein A. The protein was expressed in Escherichia coli.…”
Section: Methodsmentioning
confidence: 99%
“…3 ' 4 Other investigators have observed that t-PA can reduce neurologic damage when given as long as 45 minutes after stroke onset. 5 Hemorrhagic side effects are of major concern, but in these animal models of stroke such side effects have not been a substantial problem.…”
Section: -2mentioning
confidence: 99%